Funeral rites of the amaXhosa as therapeutic procedures compared to crisis intervention : an anthropological-descriptive evaluation - Solomon, Angela Ntombizodwa Nokuphila (Rhodes University, Faculty of Humanities, Department of Psychology, 1987)
This study was undertaken in an attempt to investigate the analogy between the Crisis Intervention Model and the Funeral Rites of the amaXhosa. The latter group includes both traditional as well as Western Christian elements. The study was confined to the geographical area of Ciskei and more specifically the villages in and around Peddie and Ndevana near Zwelitsha, as regards traditional people, and the Black townships of Zwelitsha and Whittlesea,as regards more Westernized people. It is, however, the contention of the study that experiences discussed here are common to Blacks in South Africa irrespective of ethnicity. The justification for this generalisation is based on anthropological commonalities as well as historical vicissitudes among Blacks in Southern Africa. For instance, ritual slaughter performed after death in propitiation with the ancestors is known among all Blacks in South Africa. Also the Politico-historical events as well as socio-economic developments in the country affect Blacks in a more or less similar manner. For example, the changing family structure among Blacks, because of changes from one type of economy to another, is a social process affecting all Blacks in Southern Africa - in particular the working class (Colin Murray, 1980). The Funeral rites under study are postulated as possessing elements of therapeutic and practical value which result in the alleviation of grief and the encouragement of full acceptable means of mourning. The study is chiefly descriptive and anthropological material has been used. Recordings were made from participant observation whenever there was a funeral in the area studied. Information about funerals is easily obtainable as these are announced over Radio Ciskei and Radio Xhosa every evening. Mourners and interveners were interviewed. The former to elicit the needs they had felt, the latter to elicit the needs they had perceived the former to have. The Crisis Intervention Model is fairly simple to understand and uses practical theory. Therefore, it is not surprising that there should be elements of similarity between this model and the funeral rites of the amaXhosa as both deal with people in need of support. These funeral rites are rooted in a culture which has as one of its crucial aspects intimate, face-to-face interaction of its members in constant exchange as regards both emotional support and services. These "credit networks" ensure that a person is never bereft of emotional support. Moreover, temporary services are always accorded to a person in crisis. An effort has been made to relate the Crisis Intervention Model to the South African context of Blacks (both traditional as well as Christian). By necessity this has meant looking at all cultural dimensions of Black society - historical, political, economic and cultural, in order to provide a clearer picture of the people under study. That is, human psychological experiences of grief and mourning are seen as processes related to and developing within the concrete everyday realities. Some of the experiences described have been personally witnessed by the researcher in her personal involvement with cultural practices. Funerals are, of necessity, sad occasions and this study, using participant observation methods sometimes brought on sad memories of the researcher's own losses of loved ones. In the discussion a comparison was made between the traditional methods of grief work, the Crisis Intervention theory and the mourner studied and it was found that these rites do indeed, contain therapeutic and practical elements of dealing with grief and mourning, comparable to the Crisis Intervention Model. Finally in the conclusior a proposal for further areas of study in this field was suggested.
Keywords: Xhosa (African people) -- Funeral customs and rites; Xhosa (African people) -- Psychology; Bereavement -- Psychological aspects; Mourning customs -- South Africa